Nan-O-Style – experiments and arts - Collavo, G.; Lalayev, A.; Angerer, S.; Kraml, M.; Bachner, S.; Kirchgasser, K.; Schmeel, J.; Trummer, C.; Joubert, I.A.; Geppert, M.; Schaffer, K.; Nestelbacher, R.; et al. (Open Schools Journal for Open Science, 2020)
In this project, high school students (aged 16-17) tested various protocols of experiments in nanotechnology and evaluated them whether such experiments could also be performed by middle school students (aged 11-15) or even elementary school students (aged 6-10). Protocols pre-selected and provided by the instructing team consisting of Sciencetainment and the Department of Biosciences, University of Salzburg were applied. Laboratory techniques such as thin-layer chromatography, measuring the contact angle by high-resolution 3D microscopy and analyzing and constructing surface layers represented some of the experiments performed. Moreover, students produced short video clips and images and designed photo-collages out of microscopic and electron microscopic pictures. Hence, the school students acquired a number of soft skills during this special science day.